2015
DOI: 10.4161/21505594.2014.978721
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an oral infection model resembling the periodontal pocket in a perfusion bioreactor system

Abstract: Periodontal infection involves a complex interplay between oral biofilms, gingival tissues and cells of the immune system in a dynamic microenvironment. A humanized in vitro model that reduces the need for experimental animal models, while recapitulating key biological events in a periodontal pocket, would constitute a technical advancement in the study of periodontal disease. The aim of this study was to use a dynamic perfusion bioreactor in order to develop a gingival epithelial-fibroblast-monocyte organotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 75 publications
5
62
0
Order By: Relevance
“…Comparisons made between consecutive time points showed that the number of upregulated proteins was increased during the progression of the disease, an observation that is in agreement with the current literature on transcriptomics changes in the gingival tissues during the course of experimental periodontitis . Another commonly used approach for investigating differences between the studied groups is to place the differentially regulated proteins in the context of pathways or processes and place an emphasis on the proteins in the top enriched categories . Many of the top enriched GO terms in the protein localization category were “extracellular” or “secretory related.” This may not be surprising since oral biofilms are known to stimulate the secretion of several inflammatory molecules .…”
Section: Discussionsupporting
confidence: 84%
“…Comparisons made between consecutive time points showed that the number of upregulated proteins was increased during the progression of the disease, an observation that is in agreement with the current literature on transcriptomics changes in the gingival tissues during the course of experimental periodontitis . Another commonly used approach for investigating differences between the studied groups is to place the differentially regulated proteins in the context of pathways or processes and place an emphasis on the proteins in the top enriched categories . Many of the top enriched GO terms in the protein localization category were “extracellular” or “secretory related.” This may not be surprising since oral biofilms are known to stimulate the secretion of several inflammatory molecules .…”
Section: Discussionsupporting
confidence: 84%
“…Biofilms account for 80% of chronic microbial human infections, leading to increased rates of hospitalization, elevated health care costs, and increased mortality and morbidity rates (6). Upper and lower respiratory tract diseases, native valve endocarditis, chronic otitis media, eye infections, chronic wounds, diabetic foot ulcers, urinary tract infections (UTIs), and periodontitis are all biofilm-associated diseases (7)(8)(9)(10)(11)(12). Biofilms can also develop on abiotic surfaces, including medical devices such as orthopedic prostheses, artificial cardiac valves, coronary stents, intravascular and urinary catheters, neurosurgical, cochlear, and breast implants, dentures, and ventricularassist and ocular devices (13).…”
Section: Introductionmentioning
confidence: 99%
“…The in vivo situation is much better reflected in three dimensional (3D) organotypic models (Antoni, Burckel, Josset, & Noel, ). The co‐culture of organotypic oral mucosa models with planktonic bacteria, monospecies biofilms, or even multispecies biofilms facilitated in vitro studies, which explored the impact of host–microbe interactions (T. Ahlstrand et al, ; Andrian, Grenier, & Rouabhia, ; Bao, Papadimitropoulos, Akgul, Belibasakis, & Bostanci, ; Buskermolen et al, ; Diaz et al, ; Gursoy, Pollanen, Kononen, & Uitto, ; Pinnock, Murdoch, Moharamzadeh, Whawell, & Douglas, ). In order to study the soft‐tissue‐implant interface, Chai et al .…”
Section: Introductionmentioning
confidence: 99%